Short and Long Term Effects of Splenectomy on Memory B Cell Level in Children - Paul, Shantona Rani; Islam, Mohammad Saiful; Ali, Md Nowshad; Shahid, SM Ahsan; Hossain, Md Zamil (TAJ: Journal of Teachers Association, 2022)
Introduction: Splenectomy has long been used to treat benign hematological abnormalities such as immune thrombocytopenia (ITP), some hemolytic anemias- especially hereditary spherocytosis and thalassemia, and prehepatic portal hypertension. The discovery that splenectomized individuals are more vulnerable to encapsulated organism infection has been attributed to the spleen's lack of filtration and the development of anticarbohydrate antibodies. Recent research in such splenectomized patients suggests that the lack of this specific anticarbohydrate antibody in these participants is attributable to a decreased number of Memory B cells (a subgroup of B lymphocytes in charge of T-independent responses). Traditional vaccinations, which are given to splenectomized patients to protect them from being infected by encapsulated organisms, can only act in the presence of both the spleen and its functioning marginal zone. As a Result, the study will look at the level of memory B cells in the blood after three months and 1-year post-splenectomy. Aim of the study: The objective of the study was to observe the short- and long-term effects of splenectomy on memory B cells in children. Methods: This prospective case-control study was conducted at the Pediatric Surgery Department of Bangabandhu Sheikh Mujib Medical University, Bangladesh. The study duration was one year, from July 2015 to August 2016. A total of 26 children were selected through a purposive sampling technique for this study, where the control group consisted of 10 children, and the case group consisted of 16 splenectomized children. Result: Among the case group participants, 56.25% were from the oldest age group of 12-15 years, and 37.5% were from the age group of 8-11-years. Male prevalence was high in both the control and the case group. Beta thalassemia was the primary indication for splenectomy for 81.25% of case group patients. Mean B lymphocyte was 39700.2 in the control group, 3655.3 at the 3-month follow-up of case group participants, and 3381.7 for those who had follow-up1-year after splenectomy. The mean amount of IgM memory B cells in the control group was 17.92%; at the 3-month follow-up of the case, it was 18.96%, and at the 1-year follow-up, it was 4.34%. Conclusion: In post-splenectomy individuals, immunological constitutions in memory B cells do not support a T-independent response and, therefore, vaccination. TAJ 2022; 35: No-1: 39-44